Section B.3 Trigonometry Reference
The Unit Circle.
Subsection B.3.1 Definitions of the Trigonometric Functions
Unit Circle Definition.
\(\sin \theta = y\) | \(\cos \theta = x\) |
\(\ds\csc \theta = \frac1y\) | \(\ds\sec \theta = \frac1x\) |
\(\ds\tan \theta = \frac yx\) | \(\ds\cot \theta = \frac xy\) |
Right Triangle Definition.
\(\ds\sin \theta = \frac{\text{O} }{\text{H} }\) | \(\ds\csc \theta = \frac{\text{H} }{\text{O} }\) |
\(\ds\cos \theta = \frac{\text{A} }{\text{H} }\) | \(\ds\sec \theta = \frac{\text{H} }{\text{A} }\) |
\(\ds\tan \theta = \frac{\text{O} }{\text{A} }\) | \(\ds\cot \theta = \frac{\text{A} }{\text{O} }\) |
Subsection B.3.2 Common Trigonometric Identities
- \(\displaystyle \sin ^2x+\cos ^2x= 1\)
- \(\displaystyle \tan^2x+ 1 = \sec^2 x\)
- \(\displaystyle 1 + \cot^2x=\csc^2 x\)
- \(\displaystyle \sin 2x = 2\sin x\cos x\)
- \begin{align*} \cos 2x \amp = \cos^2x - \sin^2 x \amp \amp \\ \amp = 2\cos^2x-1 \amp \amp \\ \amp = 1-2\sin^2x \amp \amp \end{align*}
- \(\displaystyle \tan 2x = \frac{2\tan x}{1-\tan^2 x}\)
- \(\displaystyle \sin\left(\frac{\pi}{2}-x\right) = \cos x\)
- \(\displaystyle \cos\left(\frac{\pi}{2}-x\right) = \sin x\)
- \(\displaystyle \tan\left(\frac{\pi}{2}-x\right) = \cot x\)
- \(\displaystyle \csc\left(\frac{\pi}{2}-x\right) = \sec x\)
- \(\displaystyle \sec\left(\frac{\pi}{2}-x\right) = \csc x\)
- \(\displaystyle \cot\left(\frac{\pi}{2}-x\right) = \tan x\)
- \(\displaystyle \sin(-x) = -\sin x\)
- \(\displaystyle \cos (-x) = \cos x\)
- \(\displaystyle \tan (-x) = -\tan x\)
- \(\displaystyle \csc(-x) = -\csc x\)
- \(\displaystyle \sec (-x) = \sec x\)
- \(\displaystyle \cot (-x) = -\cot x\)
- \(\displaystyle \sin^2 x = \frac{1-\cos 2x}{2}\)
- \(\displaystyle \cos^2 x = \frac{1+\cos 2x}{2}\)
- \(\displaystyle \tan^2x = \frac{1-\cos 2x}{1+\cos 2x}\)
- \(\displaystyle \sin x+\sin y = 2\sin \left(\frac{x+y}2\right)\cos\left(\frac{x-y}2\right)\)
- \(\displaystyle \sin x-\sin y = 2\sin \left(\frac{x-y}2\right)\cos\left(\frac{x+y}2\right)\)
- \(\displaystyle \cos x+\cos y = 2\cos \left(\frac{x+y}2\right)\cos\left(\frac{x-y}2\right)\)
- \(\displaystyle \cos x-\cos y = -2\sin \left(\frac{x+y}2\right)\sin\left(\frac{x-y}2\right)\)
- \(\displaystyle \sin x\sin y = \frac12 \big(\cos(x-y) - \cos (x+y)\big)\)
- \(\displaystyle \cos x\cos y = \frac12\big(\cos (x-y) +\cos (x+y)\big)\)
- \(\displaystyle \sin x\cos y = \frac12 \big(\sin(x+y) + \sin (x-y)\big)\)
- \(\displaystyle \sin (x\pm y) = \sin x\cos y \pm \cos x\sin y\)
- \(\displaystyle \cos (x\pm y) = \cos x\cos y \mp \sin x\sin y\)
- \(\displaystyle \tan (x\pm y) = \frac{\tan x\pm \tan y}{1\mp \tan x\tan y}\)